Penyidikan Tindak Pidana Perpajakan Berdasarkan Peraturan Menteri Keuangan Nomor 17 Tahun 2025 - Wibowo, Agung Satryo; Darmawan, Didit; Putra, Arif Rachman; Hardyansah, Rommy; Jauhari, Muhammad Alvin (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Law enforcement in the field of taxation plays a crucial role in ensuring compliance and optimizing state revenue. Minister of Finance Regulation Number 17 of 2025 serves as a legal foundation for the investigation of tax crimes, aiming to uphold the principles of transparency, accountability, and human rights protection. This study examines two main aspects: the implementation of tax crime investigations and the practical challenges encountered, as well as how taxpayers' rights are protected under the regulation. The findings indicate that although the regulation contains comprehensive procedural standards and safeguards, several obstacles persist in practice, including legal interpretation issues, limited resources, and socio-cultural or bureaucratic barriers. It is recommended that derivative regulations be refined, the competence of law enforcement officers be improved, and oversight mechanisms be strengthened to ensure fair investigation processes for both the state and taxpayers. Continuous reform is necessary for the national taxation system to effectively address legal challenges and meet public needs in a balanced manner.